RELEVANSI HAK VETO DEWAN KEAMANAN DENGAN TUJUAN PEMBENTUKAN PERSERIKATAN BANGSA - BANGSA - Ummi Yusnita; Ramona Nova; Aisyah Lutfiah; Nur arisman (Cahaya Ilmu Bangsa, 2023)
The veto power held by the United Nations Security Council is a crucial and controversial issue, especially recently when a resolution produced by the UN General Assembly was vetoed by one of the member countries of the permanent security council, namely the United States, regarding the ceasefire in Gaza. This article aims to find out whether the veto right is still relevant to the aim of establishing the UN. The research method used in this research is normative juridical with a descriptive analysis approach. The results of the research show that the veto right possessed by the Security Council is no longer relevant to the aim of establishing the UN, namely to achieve world peace, especially in the Palestinian – Israeli conflict, where to date Palestinian civilian casualties have reached 20,000 people, this is proof that the UN's goals are far away. From the words achieved, the UN Security Council's task has not been achieved, namely guarding international peace and security, in fact, there are more and more casualties in Gaza because America uses its veto power to refuse a ceasefire